A study of cases of rupture uterus in a tertiary medical college of Jharkhand, India - Kamal, Samarina; Singh, Shashibala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine rupture is a grave condition which is almost fatal for fetus. The most common risk factor for the uterine rupture is previous uterine surgery. Other major factors are obstructed labor, multiparity, use of uterotonic drugs, placenta percreta and rarely intrauterine manipulations such as internal podalic version and breech extraction. Methods: This study was conducted over a period from March 2014 to September 2015, in the Department of Gynecology and Obstetrics, RIMS Ranchi, Jharkhand. All cases of rupture uterus, who were either admitted with or who developed this complication in the hospital, were included in the study. Results: There were 80 cases of rupture uterus out of 10474 deliveries. The incidence of rupture uterus was more (97.5%) in cases who had no previous antenatal checkup at all. Most of cases of previous caesarean section scar rupture during labour was lower segment caesarean section scar (94.11%). The most common causes of traumatic rupture were injudicious use of oxytocics (75%). Majority of cases of rupture uterus were of complete type (96.25%). The most frequent site of rupture was in the anterior wall of lower segment in 68.75% of cases. The maternal mortality rate cases of rupture uterus were 3.75%. Conclusions: Proper antenatal care and updated training courses of health care providers should be stressed to prevent this catastrophic but avoidable complication.